2012
DOI: 10.1148/radiol.12111374
|View full text |Cite
|
Sign up to set email alerts
|

Serial CT Findings ofMycobacterium massiliensePulmonary Disease Compared withMycobacterium abscessusDisease after Treatment with Antibiotic Therapy

Abstract: Common CT findings of M massiliense diseases overlap with those of M abscessus disease. However, responses to antibiotic treatment are much different; in M massiliense disease, negative sputum conversion is accomplished in all patients and serial CT scans show improvement in most patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
59
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 17 publications
(33 reference statements)
4
59
0
1
Order By: Relevance
“…54 Separately, CT scan fi ndings before and aft er therapy showed that most patients with Mam had improvement compared with only one-third of patients with Maa . 55 As noted previously, differing response to macrolide-based regimens among subspecies of M abscessus relates to the presence or absence of a truncated erm gene. [42][43][44] Th is raises the question of whether diff erent macrolides equally aff ect erm induction.…”
Section: Choice Of Macrolidementioning
confidence: 84%
“…54 Separately, CT scan fi ndings before and aft er therapy showed that most patients with Mam had improvement compared with only one-third of patients with Maa . 55 As noted previously, differing response to macrolide-based regimens among subspecies of M abscessus relates to the presence or absence of a truncated erm gene. [42][43][44] Th is raises the question of whether diff erent macrolides equally aff ect erm induction.…”
Section: Choice Of Macrolidementioning
confidence: 84%
“…The fibrocavitary form (previously called the upper lobe cavitary form) is defined by the presence of cavitary opacities, mainly in the upper lobes. The nodular bronchiectatic form is defined by the presence of bronchiectasis and multiple nodules upon chest HRCT, regardless of the presence of small cavities in the lungs (44,45).…”
Section: Methodsmentioning
confidence: 99%
“…The fibrocavitary form of the disease (previously called the upper lobe cavitary form) was defined by the presence of cavitary opacities, mainly in the upper lobes. The nodular bronchiectatic form was defined by the presence of bronchiectasis and multiple nodules on chest HRCT scans, irrespective of the presence of small cavities (diameters of Ͻ3 cm) in the lungs (33,34).…”
Section: Methodsmentioning
confidence: 99%